2000
DOI: 10.1007/s002130000542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of central 5-hydroxytryptamine depletion on sensitivity to delayed and probabilistic reinforcement

Abstract: These results provide additional evidence that central 5-HTergic mechanisms are involved in time discounting, but provide no evidence for a similar role of 5-HT in rats' sensitivity to probabilistic reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
143
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(150 citation statements)
references
References 32 publications
4
143
3
Order By: Relevance
“…Disruption of 5-HT function by intra-raphé injections of 5,7-dihydroxytryptamine promotes impulsive choice for the smaller immediate reward (Wogar et al 1993;Ho et al 1998;Mobini et al 2000). Similar effects of 5-HT depleting lesions on impulsivity have been inferred from other operant paradigms, including a conditional go/no-go visual discrimination task (Harrison et al 1999) and reinforcement schedules with low response rates (Wogar et al 1993).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Disruption of 5-HT function by intra-raphé injections of 5,7-dihydroxytryptamine promotes impulsive choice for the smaller immediate reward (Wogar et al 1993;Ho et al 1998;Mobini et al 2000). Similar effects of 5-HT depleting lesions on impulsivity have been inferred from other operant paradigms, including a conditional go/no-go visual discrimination task (Harrison et al 1999) and reinforcement schedules with low response rates (Wogar et al 1993).…”
Section: Discussionmentioning
confidence: 59%
“…Post-mortem analysis revealed that 5-HT utilization (ratio of the 5-HT metabolite, 5-hydroxyindoleacetic acid to 5-HT) in the right frontal cortex increased proportionally with impulsive responding during the intertrial interval. These data are apparently at odds with studies where profound and global central depletion of 5-HT following lesions of the ascending 5-HTergic projections induced by the selective neurotoxin, 5,7-dihydroxytryptamine, increase impulsive behavior on both a 5-CSRT task (Harrison et al 1997a,b) and a delayof-reward choice procedure (Wogar et al 1993;Mobini et al 2000).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, recent studies with human volunteers have found that ATD increases impulsive and aggressive behavior, although these effects appear to depend on individual differences in impulsive personality traits (Cherek and Lane, 1999;LeMarquand et al, 1999;Dougherty et al, 1999;Bjork et al, 2000;Marsh et al, 2002;Crean et al, 2002). Findings from studies with clinical human populations are corroborated by an extensive number of animal studies, which suggest that impulsive choice in delaydiscounting paradigms and premature responding in choice reaction-time tasks implicate changes in the 5-HT system (Wogar et al, 1993;Harrison et al, 1997a, b;Puumala and Sirvio, 1998;Koskinen et al, 2000;Mobini et al, 2000;Dalley et al, 2002;Passetti et al, 2003;Winstanley et al, 2003;Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 98%